Upper Trishuli-2 Hydroelectric Project - Dhungana, Santosh (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Not Available.HYDRO Nepal JournalJournal of Water, Energy and EnvironmentIssue: 19Page: 70